If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g + 4h = 34 Solving 7g + 4h = 34 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4h' to each side of the equation. 7g + 4h + -4h = 34 + -4h Combine like terms: 4h + -4h = 0 7g + 0 = 34 + -4h 7g = 34 + -4h Divide each side by '7'. g = 4.857142857 + -0.5714285714h Simplifying g = 4.857142857 + -0.5714285714h
| -126=6(3+3b) | | 4w^3+w^2-5w= | | 8-1-y=-7 | | 12(z-2)=3z+1 | | 10p+2=102 | | 18+5.5m=73 | | 23935.91*(1)+(0.34/12)=a | | 8(9c-1)-16=70c+8 | | -3(-5x-4)=6(x-1) | | 23935(1+0.34/12)=a | | .71x=35 | | 8(y-3)=5y-36 | | 4(-15-3p)-4(p+5)= | | -7(2+3a)=-98 | | 17+6x=-6x-7 | | 23935(1+0.34/12)= | | 2(3n+4)=7(4n+2)+4 | | 5(4c-1)-5=15c+5 | | .666(3x+4)=24 | | (x)2+2x-15=2x-1 | | 10x-6x+168=10x+84 | | tn=3n+8 | | -2(t+3)=6 | | 2(x-4)=-x-4 | | 7(3n+1)=6(2n+3)+2 | | 4b+3a=18 | | -5(-6x-3)=375 | | 4x-55x-11=198 | | 90=6(2n-1) | | 3G-3=3(7-1g) | | .7x-4.6=.3 | | 447+z=-261 |